2013
DOI: 10.5121/ijans.2013.3301
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Enhanced Routing Protocols for Manets

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Up to now the routing mechanisms still the major challenge of MANETs, where the performance of all the proposed routing mechanisms did not reach to the anticipated level [8,9]. According to routing information update mechanism, MANET routing schemes can be classified into two classes: proactive and reactive schemes [10][11][12][13]. Most previous studies have concluded that performance of reactive schemes more efficient than proactive schemes especially when MANET is subjected to high dynamic topology [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now the routing mechanisms still the major challenge of MANETs, where the performance of all the proposed routing mechanisms did not reach to the anticipated level [8,9]. According to routing information update mechanism, MANET routing schemes can be classified into two classes: proactive and reactive schemes [10][11][12][13]. Most previous studies have concluded that performance of reactive schemes more efficient than proactive schemes especially when MANET is subjected to high dynamic topology [14,15].…”
Section: Introductionmentioning
confidence: 99%